Conflict and Harmony Between Desa Adat and the Bali Provincial Government Following the Enactment of the Regional Regulation on Customary Village 2019 - I Putu Gede Sridana; I Wayan P. Windia; I Nyoman Suarka; Ni Luh Sutjiati Beratha (Jurnal Kajian Bali (Journal of Bali Studies), 2024)
The Bali Provincial Government collaborates with desa adat (customary village) to enhance their strength and resilience, notably through the enactment of Province of Bali Regulation Number 4 of 2019. However, excessive regulatory impact may diverge from this goal. This study explores the ideological framework shaping interactions between desa adat and the government post-regulation. Using a qualitative methodology, data were collected through literature review, observations, and in-depth interviews. The findings draw on theories of hegemony, ideology, discourse, and the power of knowledge. Hidden ideologies of power, capital, and religion influence these interactions. The regulation's uniform framework on diverse desa adat leads to resistance and inefficiency, reflecting hegemonic control and the use of ideology and knowledge to legitimize power. This article contributes to developing legislation that empowers the desa adat while maintaining their unique characteristics.